Improvement of Brake Caliper Production Process by Using Motion and Time Study Case study ADVICS Manufacturing (Thailand) Co., Ltd. - Sriwattana, ์Nitisak; Sangbuathao, Supachai; Kamya, Pisal (Journal of Engineering and Industrial Technology, Kalasin University, 2024)
ADVICS Manufacturing (Thailand) Co., Ltd. Engaging in the business of producing and distributing brake systems and automobile parts. It is an automotive parts manufacturing industry that organizes efficient production operations and produces products of the highest quality. Currently, it is found that there are problems in the production of brake caliper production systems. It takes longer to produce than the standard time set by the company. Makes the production volume produce brake calipers. Not according to the goals set by the company. Due to the movement of workers on the production line, brake calipers spend time in unnecessary movements. There is wasted working time. The researcher has invented a method to reduce movement and reduce production time to help solve the problem of brake caliper production. The objectives of this research are 1) to reduce brake caliper manufacturing time 2) to increase the production of brake calipers. The study of manufacturing process of brake calipers. By using the form of time recording (Check Sheet), motion study (Motion study), time study (Time study), The data was collected from October to November 2022 and compare the data before and after. The results showed that movement of workers in the brake caliper production line was reduced from 50 seconds to 47 seconds accounted for 6 percent, and production was increased from 122 pieces per hour per month to 130 pieces per hour per month. accounted for 6.15 percent.